2003
DOI: 10.1029/2001rs002514
|View full text |Cite
|
Sign up to set email alerts
|

Radio tomographic imaging as an aid to modeling of ionospheric electron density

Abstract: [1] Models of the ionosphere, used in applications for the prediction or correction of propagation effects on practical radio systems, are often inadequate in their representation of the structure and development of large-scale features in the electron density. Over northern Europe, characterization of the main trough presents particular problems for such empirical or parameterized models and hence for radio propagation forecasting and ionospheric mapping. Results are presented from a study aimed at investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…However, the resultant equations have had only limited application because of the wide day‐to‐day variability in the location and form of the feature. More recently, the radio tomography technique has been shown to be particularly adept at imaging the large‐scale horizontal spatial structure of the trough [ Pryse et al , 1993; Kersley et al , 1997; Dabas and Kersley , 2003; Pryse , 2003], a success that has been exploited here in the characterization of the form of the structure by means of a number of carefully defined parameters.…”
Section: Introductionmentioning
confidence: 99%
“…However, the resultant equations have had only limited application because of the wide day‐to‐day variability in the location and form of the feature. More recently, the radio tomography technique has been shown to be particularly adept at imaging the large‐scale horizontal spatial structure of the trough [ Pryse et al , 1993; Kersley et al , 1997; Dabas and Kersley , 2003; Pryse , 2003], a success that has been exploited here in the characterization of the form of the structure by means of a number of carefully defined parameters.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that radio tomography has an important role to play in the validation of ionospheric models, not only the empirical and parameterized types used for the mitigation of propagation effects on practical radio systems [ Dabas and Kersley , 2003], but also the first‐principles models based on solution of the underlying physical equations of the coupled ionosphere and thermosphere [ Idenden et al , 1998]. While the earlier study was confined to comparisons with observations from a single chain of stations, the results presented here demonstrate the potential of using observations from multiple stations in the validation of the wider geographic aspects of the model behavior.…”
Section: Discussionmentioning
confidence: 99%
“…There are many techniques used to probe the ionosphere that includes the earth based radio techniques: vertical sounders, incoherent scatter radar, etc., as well as space-based techniques: Geostationary satellites, GPS satellites, LEO satellites and in situ measurements. Ionospheric scientists are also using new techniques such as computed tomography [6][7][8] , occultation [9,10] and University of New Brunswick (UNB) ionospheric modeling technique [11] .…”
Section: Total Electron Content (Tec)mentioning
confidence: 99%